1999
DOI: 10.1210/jcem.84.4.5728
|View full text |Cite
|
Sign up to set email alerts
|

Several Mutations in the Melanocortin-4 Receptor Gene Including a Nonsense and a Frameshift Mutation Associated with Dominantly Inherited Obesity in Humans

Abstract: The melanocortin-4 receptor gene (MC4-R) has been implicated in weight regulation. Recently, two independent groups reported frameshift mutations associated with a dominant form of obesity (1, 2). We screened the coding region of the MC4-R in 306 extremely obese children and adolescents (mean body mass index: BMI 34.4 +/- 6.6 kg/m2), 25 healthy underweight students (mean BMI 17.1 +/- 0.8 kg/m2), 52 normal weight individuals (mean BMI 22.0 +/- 1.0 kg/m2), 51 inpatients with anorexia nervosa (AN, DSM IV criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
214
1
8

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 361 publications
(235 citation statements)
references
References 0 publications
12
214
1
8
Order By: Relevance
“…All three were previously reported: a G-A nucleotide change at position 307 resulting in the substitution of Val103 with Ile, 9 a C335T single nucleotide change which leads to a Thr112Met aminoacid substitution 18 and finally the Ile251Leu substitution resulting from the A751C nucleotide change. 19 In our study, the frequencies of the rare alleles of the latter two polymorphisms (Thr112Met 0.46%, Ile251Leu 0.92%) are in line with those reported previously. Based on metaanalysis of all studies listed in Table 4, there is no significant difference between controls and cases for these two polymorphisms.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…All three were previously reported: a G-A nucleotide change at position 307 resulting in the substitution of Val103 with Ile, 9 a C335T single nucleotide change which leads to a Thr112Met aminoacid substitution 18 and finally the Ile251Leu substitution resulting from the A751C nucleotide change. 19 In our study, the frequencies of the rare alleles of the latter two polymorphisms (Thr112Met 0.46%, Ile251Leu 0.92%) are in line with those reported previously. Based on metaanalysis of all studies listed in Table 4, there is no significant difference between controls and cases for these two polymorphisms.…”
Section: Discussionsupporting
confidence: 93%
“…Three adults were heterozygous for the Val103Ile variant and one for the Thr112Met variant, two previously reported polymorphisms. 9,18 Neither the third known polymorphism, Ile251Leu, 19 nor MC4R analysis in Belgian obese children and adults S Beckers et al pathogenic mutations in MC4R were found in our cohort of morbidly obese adult patients. The cohort of 123 children and adolescents was also screened for MC4R mutations.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…Polymorphisms in the MC4-R gene (Val103Ile, Ile251Leu) and AgRP gene (Ala67Thr) have also been found in AN patients. Although the occurrence of the MC4-R polymorphism was not different from a control population (Hinney et al, 1999), the AgRP polymorphism occurred more frequently in a population of AN patients compared to controls (Vink et al, 2001) and was associated with low body weight in two other populations (Argyropoulos et al, 2002;Marks et al, 2004).…”
Section: Introductionmentioning
confidence: 67%
“…Polymorphisms in the MC4R gene (Val103Ile, Ile251Leu) and AGRP gene (Ala67Thr) have also been described in populations of AN patients. Although the occurrence of the MC4R polymorphisms was not different from a control population [24], the AGRP polymorphism occurred more frequently in a population of AN patients as compared to controls [47] and was associated with low body weight in two other populations [3,33].…”
Section: Discussionmentioning
confidence: 60%